Keefektifan Model Pembelajaran Berbasis Masalah (PBM) dan Konvensional untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran IPS - Affadil, Muhammad; Ease Arent; Anggiat Sinurat (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This research aims to determine the effectiveness of problem-based and conventional learning models on students' critical thinking skills in social studies (Geography) learning at SMP Negeri 1 Gebang District. The research method used was quasi-experimental with a population of 2 parallel classes. The sampling technique is carried out by sampling, where class VII-1 is the experimental class and VII-2 is the control class. Data analysis technique using ANAVA 2 Line (univariate) with the help of SPSS 25.00 for windows application. Data collection techniques use test instruments in the form of description options. The results of data analysis were obtained: (1) the problem-based learning model affected students' critical thinking skills with a significance of 0.000 < 0.05 with an average score of 87.55; (2) conventional learning models affect students' critical thinking skills with ANOVA test results with significance of 0.000< 0.05 with an average score of 77.29; and (3) There is an interaction between the problem-based learning model and the conventional learning model in influencing students' critical thinking skills with a significant level of 0.000 < 0.05 where the average score produces a positive score of 21.46 (interaction of the PMB model with the Conventional Model) and the average value produces a positive score of 12.56 (interaction of the conventional model against the PBM model) in the Tukey Test follow-up test.